Phenomenon : everything you need to know about the paranormal - Browne, Sylvia (New American Library, 2006)
Presents an A-to-Z compendium of elements in the spiritual and supernatural world that influence mortal life, exploring such phenomena as numerology, reincarnation, and ghosts.